Highly efficient electrochemical energy conversion in a 3D hollow microenvironment: towards on-a-chip sensor applications. Issue 38 (21st September 2020) - Minatogau Ferro, Letícia Mariê; de Barros, Anerise; Zaparoli Falsetti, Luís Otávio; Corrêa, Cátia Crispilho; Merces, Leandro; Bof Bufon, Carlos César
Abstract : Multipurpose analytical platforms that can reliably be adapted to distinct targets are essential nowadays. Abstract : Multipurpose analytical platforms that can reliably be adapted to distinct targets are essential nowadays. Here, the conception, characterization, and application of ultracompact three-dimensional (3D) electroanalytical platforms based on self-curled nanomembranes are presented. The electrodes of all devices are deterministically integrated on the inner walls of a hollow microtube – a task that cannot be accomplished by approaches other than the successful manipulation of nanomembranes. The on-a-chip architecture demonstrated here allows picoliter-sampling, ensures a well-controlled environment for complex analysis, and improves the catalytic activity by enhancing ion transport and electron transfer rates. As a proof-of-concept, these features are exploited to create a new device to monitor the chemical oxidation of nicotinamide adenine dinucleotide (NADH) – a biomolecule related to human neurodegenerative diseases. Without any electrode functionalization, the nanomembrane-based 3D-devices exhibit sensitivity per unit area compared to the state-of-the-art NADH sensors. Envisioning lab-on-a-chip purposes, the reduced electrode footprint area of the 3D-device makes its sensitivity per area on a chip even higher, attesting the potential of this platform towards further energy conversion applications.